KONSTRUKSI LAPORAN KEUANGAN BERDASARKAN PERATURAN MENTERI KOPERASI & UKM PADA KOPERASI SYARIAH X - Leli Saputri; Nur Fitriyah; Lalu Takdir Jumaidi (Bisnis-Net, 2023)
The purpose of this study is to analyze and provide an overview to cooperative specialists related to the financial statements of the Sharia Cooperative X based on SAK ETAP and PSAK 101. The research uses descriptive data analysis techniques with a qualitative approach. The data source comes from primary data in this study obtained from observations on the Sharia Cooperative X and interviews with the managers of the Sharia Cooperative X and secondary data, namely documentation in the form of financial statements of the Sharia Cooperative X Period 2021. From the information obtained by researchers, both through documentation and observation and interviews with cooperative treasurers, it was obtained that financial statements compiled by cooperative treasurers have not conformed to financial accounting standards (SAK) for sharia cooperatives, namely SAK ETAP and PSAK 101. Sharia cooperative X comprises only three financial statements (balance reports, profit reports, and cash flow reports), this is not in accordance with the contents contained in SAK ETAP and PSAK 101 which Sharia entities including Sharia cooperatives are required to compile balance sheet reports, business calculation reports, equity changes reports, cash flow reports, source reports and distribution of zakat funds, source reports and use of virtue funds, and records on financial statements (CALK). The next step after knowing this, researchers will construct financial statements as an overview of the financial statements of the Sharia Cooperative X in accordance with financial accounting standards (SAK) for Sharia cooperatives (SAK-ETAP and PSAK 101).